Marine Ecotourism Architecture - Ahmad Wahidiyat Haedar; Taufiq Natsir; Raeny Tenriola Idrus; Muhammad Reza Hasrul (Universitas Negeri Makassar, 2021)
Tourism is the largest industry and the leading sector of multidimensional development that attracts attention to be developed by many archipelagic countries and regions. Marine ecotourism architecture is the right choice to be developed in an integrated manner based on its components in the form of attractions, accessibility, accommodation, amenities, and tourism, which is abbreviated as 5A tourism. This research article describes an architectural model prototype for marine ecotourism development based on Google SketchUp and Lumion Island Larea-rea as a marine tourism destination in the East Coast Region of South Sulawesi Province, Indonesia. This type of Research and Development applies the ADDIE (Analysis, Design, Development, Implementation, Evaluation) approach. Observation and interview techniques were used in field research to collect data and information which were analyzed descriptively. The results of the research in the form of a prototype architectural model design for developing Larea-rea Island tourism destinations based on 5A show natural and well-maintained ecological attractions because the white sand beaches have not been polluted with clear seawater and natural coral reefs. The architectural concept of marine ecotourism is a miniature island tourism destination that has an attraction in the form of a miniature mangrove forest to prevent beach abrasion and the local cultural theme amenity is reflected in the architecture of